The Effect of Foreign Exchange Transaction on the Performance of Nigerian Banks - Manyo, Takon Samuel; Sabina, Nsofor Ebele; Ugochukwu, Ugwuegbe Sebastine (IJRDO - Journal of Business Management, 2016)
This study investigated the effect of foreign exchange transaction on the profitability of Nigerian banks for the period of 2010 to 2014. The study employed annual data generated from the annual report of ten (10) publicly quoted banks in Nigeria. To test for the properties of panel data, Levin, Lin and Chu (2002), Breitung (2000), Im, Pesaran and Shin (2003), Hadri (2000) and Maddala and Wu (1999) test of panel unit root were deployed. Based on the popularity of the result we concluded that the variables are integrated of order one I(1). The result of Kao panel co-integration test indicates that there exists a long run relationship between the variables under study. The result of the DOLS revealed that foreign exchange income has a negative and insignificant effect on the profitability of Nigerian banks for the period. Total asset which was used as a control variable was shown to exert positive impact on the profitability of Nigerian banks, while total equity has a negative effect on profitability of banks in Nigeria for the same period under study. The studies recommend that CBN and other monetary authorities should monitor the activities of the banks to ensure that they don’t charge high premium for selling or buying foreign exchange to their customers. Banks should enhance their assets base so as to increase profitability.